Analysis of hemolymph proteinase 16 and serpin-3 from the hemolymph of Manduca sexta. - Christen, Jayne M. (Kansas State University, 2011)
Insect innate immune responses include prophenoloxidase activation and antimicrobial peptide production. These responses involve extracellular serine proteinase cascades that are regulated by serpins. This work involved the study of serine proteinase 16 (HP16) and serpin-3 from hemolymph of the tobacco hornworm, Manduca sexta. HP16 has an amino-terminal domain with no similarity to any characterized protein and a carboxyl-terminal S1 family serine proteinase domain. HP16 levels in plasma were highest during the wandering, prepupal, and pupal stages. HP16 mRNA levels in fat body were highest at the wandering stage. Injection of bacteria into fifth instar larvae stimulated HP16 expression. To further characterize and investigate the biological function of HP16, recombinant proteins for proHP16, two HP16 mutants, the amino-terminal domain (NT16), and three NT16 mutants were purified. Recombinant HP16 was cleaved at the predicted activation site during expression, and its amino-terminal and catalytic domains remained connected by a disulfide bond. ProHP16 in plasma was apparently activated in the presence of the microbial elicitor, zymosan. Recombinant HP16 formed a complex with serpin-1Z, indicating that it was catalytically active, but no other natural or artificial substrates were identified. Analysis of NT16 and NT16 mutants led to the discovery that multiple disulfide bond arrangements were formed in the recombinant amino-terminal domain of HP16. This work furthered the understanding of HP16 and laid a foundation for subsequent experiments involving the proteolytic activity, regulation, and biological function of HP16. Active serine proteinases in insect hemolymph are often regulated by serpins. Immunoaffinity chromatography was used to identify plasma proteinases that are inhibited by serpin-3. Four serpin-3-proteinase complexes purified from plasma were identified by immunoblot analysis as serpin-3 complexes with HP8, PAP-1, PAP-2, and PAP-3. MALDI-TOF/TOF or ESI-MS/MS analysis after separation by 1D- or 2D-PAGE confirmed serpin-3 complex formation with HP8, PAP-1, and PAP-3. ProHP8 in plasma was activated by exposure to the β-1,3-glucan curdlan and inhibited by serpin-3. Purified recombinant serpin-3 and active HP8-Xa formed an SDS-stable complex in vitro. Identification of serpin-3-proteinase complexes in plasma provides insight into proteinase targets of serpin-3 and extends the understanding of serpin/proteinase function in the immune response of M. sexta.
Keywords: Hemolymph proteinase; Serpins; Manduca sexta; Biochemistry (0487); Entomology (0353)